If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) = 3x + 62 Reorder the terms: 4(-3 + 2x) = 3x + 62 (-3 * 4 + 2x * 4) = 3x + 62 (-12 + 8x) = 3x + 62 Reorder the terms: -12 + 8x = 62 + 3x Solving -12 + 8x = 62 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 8x + -3x = 62 + 3x + -3x Combine like terms: 8x + -3x = 5x -12 + 5x = 62 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 5x = 62 + 0 -12 + 5x = 62 Add '12' to each side of the equation. -12 + 12 + 5x = 62 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = 62 + 12 5x = 62 + 12 Combine like terms: 62 + 12 = 74 5x = 74 Divide each side by '5'. x = 14.8 Simplifying x = 14.8
| s^2-1=0 | | -4(2p+2)-23=5(5p+7) | | y^2-16=0 | | y^2-100=0 | | a^2=100 | | 5x+6=30y | | 12x-18x^2=0 | | X+10=2(x-9)-x | | 12+3y=4x | | 0.60x+0.40(100-x)=140 | | x(2x-7)=15 | | 2x+18=6y | | 2(x-3)=4(x-4) | | 14x^2+45x-14=0 | | 3x+42=5x-8 | | 196-4x=41x+21 | | 64x+8y=2 | | 11-8x=35-15x | | -65-10x=7x+20 | | 3(x+6)=2x-7+x | | 2x^2+2x=3 | | m+2=6m-3 | | X^2-4x=2x+7 | | 120=16t^2 | | 7x^2+21x=0 | | x^2+4x-10=0 | | 96-2x=25x+21 | | 7x^2+21=0 | | 4x-33=x | | 4(4-w)=2(15+4y) | | 9x-7x=173-35x | | 6x+63=10x-5 |